Transonic buffet of a space launcher aileron: Fanno and Rayleigh flows analogies. Issue 4 (18th October 2021) - Gourdain, Nicolas; Dumon, Jéromine; Bury, Yannick; Molton, Pascal
Abstract : Purpose: The transonic buffet is a complex aerodynamics phenomenon that imposes severe constraints on the design of high-speed vehicles, including for aircraft and space launchers. The origin of buffet is still debated in the literature, and the control of this phenomenon remains difficult. This paper aims to propose an original scenario to explain the origin of buffet, which in turn opens promising perspectives for its alleviation and attenuation. Design/methodology/approach: This work relies on the use of numerical simulations, with the idea to reproduce the buffet phenomenon in a transonic aileron designed for small space launchers. Two numerical approaches are tested: unsteady Reynolds averaged Navier–Stokes (URANS) and large-eddy simulation (LES). The numerical predictions are first validated against available experimental data, before to be analysed in detail to identify the origin of buffet on the studied configuration. A complementary numerical study is then conducted to assess the possibility to delay the onset of buffet. Findings: The buffet control strategy is based on wall cooling. By adequately choosing the wall temperature, this work shows that it is feasible to delay the emergence of buffet. More precisely, this paper highlights the crucial role of the subsonic flow inside the boundary layer, showing the existence of upstream travelling pressure waves that are responsible for the flow coupling between both sides of the airfoil, at the origin of the buffet phenomenon. Originality/value: This paper proposes a new scenario to explain the origin of buffet, based on the use of a Fanno and Rayleigh flow analogies. This approach is used to design a control solution based on a modification of the wall temperature, showing very promising results.